International standards for quality management in tourism - Lazić, Jelena; M. Cvijanović, Janko; Ljumović, Isidora (Hotel and Tourism Management, 2013)
Tourism today is a global business in which the competition and the customers span international boundaries. Managers competing in the fierce international marketplace are increasingly concerned with a strategic view of quality. The competition is ever increasing at the global tourist services market while consumer demands are changed. Such rapid growth has also introduced new perspectives for quality management through the most famous formal quality management systems (ISO 9001, ISO 14001, ISO 18000 and ISO 22000).